Early life events may be the first steps on the multistep path to amyotrophic lateral sclerosis - Roger Pamphlett; Jane Parkin Kullmann (Scientific Reports)
Abstract A combination of multiple genetic and environmental factors appear to be required to trigger the onset of amyotrophic lateral sclerosis (ALS). Early life environmental exposures have been reported to be risk factors for a variety of adult-onset diseases, so we used data from an online international ALS case–control questionnaire to estimate whether any of these could be risk factors for the clinical onset of ALS. Responses were obtained from 1,049 people aged 40 years or more, 568 with ALS and 481 controls. People with ALS were more likely to have been born and lived longer in a country area than in a city area, to have younger parents, and to have lower educational attainment and fewer years of education. No ALS-control differences were found in sibling numbers, birth order, adult height, birth weight, parent smoking, Cesarean delivery, or age of starting smoking. In conclusion, early life events and conditions may be part of a group of polyenvironmental risk factors that act together with polygenetic variants to trigger the onset of ALS. Reducing exposure to adverse environmental factors in early life could help to lower the risk of later developing ALS.